2010
DOI: 10.1002/lt.22008
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant predictors of recovery of renal function after liver transplantation

Abstract: The Model for End-Stage Liver Disease system has given priority on the liver transplant waiting list to candidates with renal failure. This study determined the predictors of spontaneous recovery of renal function after transplantation in 1041 liver transplant recipients on renal replacement therapy (RRT) at the time of transplant (from February 2002 to January 2007). Data from these patients were obtained from the US Organ Procurement and Transplantation Network and US Renal Data System databases. Univariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
101
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(112 citation statements)
references
References 19 publications
7
101
2
2
Order By: Relevance
“…One study showed the renal nonrecovery to be as high as 32% among LT recipients who were on pre-LTRRT and received LT alone (9). However, this study did not distinguish between the candidates receiving acute and chronic RRT before LT. Our primary and secondary objectives were to assess the reversibility of AKI among those who were on acute RRT for #90 days before LT and to determine the minimum threshold of the duration of pre-LT RRT above which the risk of renal nonrecovery was substantially increased.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…One study showed the renal nonrecovery to be as high as 32% among LT recipients who were on pre-LTRRT and received LT alone (9). However, this study did not distinguish between the candidates receiving acute and chronic RRT before LT. Our primary and secondary objectives were to assess the reversibility of AKI among those who were on acute RRT for #90 days before LT and to determine the minimum threshold of the duration of pre-LT RRT above which the risk of renal nonrecovery was substantially increased.…”
Section: Introductionmentioning
confidence: 79%
“…Although candidates with AKI including HRS may recover renal function after LT (7)(8)(9), the rate and timing of renal recovery have not been very well elucidated. One study showed the renal nonrecovery to be as high as 32% among LT recipients who were on pre-LTRRT and received LT alone (9).…”
Section: Introductionmentioning
confidence: 99%
“…In these patients, early recovery of the renal graft is crucial because of the effect of posttransplant renal failure on overall transplant outcomes. [20][21][22] DGF was twice as common in the DCD- 23 In addition to the efforts by the transplant community to increase organ availability, the issue of allocating organs to maximize the benefit to individual patients should be considered. This study raises a serious dilemma about the best way to use DCD organs.…”
Section: Discussionmentioning
confidence: 99%
“…2,[4][5][6] In the other corner are data suggesting that upward of 80% of liver transplant recipients on renal replacement therapy (RRT) for fewer than 30 days go on to recover renal function after transplantation, and this indicates that at least some kidneys transplanted as part of SLK are unnecessary. 7 To whom then goes the kidney, the liver transplant candidate with renal impairment or the kidney transplant candidate?…”
Section: See Article On Page 1034mentioning
confidence: 99%
“…2,[4][5][6] In the other corner are data suggesting that upward of 80% of liver transplant recipients on renal replacement therapy (RRT) for fewer than 30 days go on to recover renal function after transplantation, and this indicates that at least some kidneys transplanted as part of SLK are unnecessary. 7 To whom then goes the kidney, the liver transplant candidate with renal impairment or the kidney transplant candidate?There is little debate about the necessity for SLK among end-stage renal disease patients with decompensated cirrhosis because these patients have no hope of recovering renal function and would not survive kidney transplantation alone; this establishes a clear role for SLK. 8 Therefore, how we frame the discussion about SLK is critical.…”
mentioning
confidence: 99%